2016
DOI: 10.1248/yakushi.16-00168
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between PK/PD of Cefepime and Clinical Outcome in Febrile Neutropenic Patients with Normal Renal Function

Abstract: The e‹cacy of cefepime (CFPM) is known to depend on the ratio of the time that the serum levels exceed the minimum inhibitory concentration (MIC) to the dosing interval (%T>MIC). The objective of this study was to clarify the relation between %T>MIC and clinical outcome of CFPM, and to identify the optimal dosage regimen. We investigated the outcome of CFPM treatment for febrile neutropenia (FN) patients with normal renal function. Treatment success was deˆned as the completion of FN therapy with CFPM only. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For febrile neutropenic patients with normal renal function or ARC, cefepime 2 g t.i.d. with 3 h of infusion was effective in several cases (Yamashita et al, 2016). A study on pediatric patients recommended a regimen of 100 mgkg-1d-1 administered as a continuous infusion to attain higher target values (de Cacqueray et al, 2022).…”
Section: Cefepimementioning
confidence: 99%
“…For febrile neutropenic patients with normal renal function or ARC, cefepime 2 g t.i.d. with 3 h of infusion was effective in several cases (Yamashita et al, 2016). A study on pediatric patients recommended a regimen of 100 mgkg-1d-1 administered as a continuous infusion to attain higher target values (de Cacqueray et al, 2022).…”
Section: Cefepimementioning
confidence: 99%
“…17 Clinical studies using cefepime doses of 4-6 g/d have been reported [18][19][20] ; higher doses may improve clinical response based on the pharmacokinetic/ pharmacodynamic principles. [21][22][23][24][25][26][27][28][29] However, high doses, such as 6 g, increase the risk of encephalopathy in a dosedependent manner, with the upper limit for trough concentrations ranging from 22 to 35 mcg/mL. 30,31 Cefepime requires a lower limit of at least 8 mcg/mL, which is equivalent to an unbound concentration time above the minimum inhibitory concentration (%fT .…”
Section: Introductionmentioning
confidence: 99%
“…Cefepime, like other β-lactams, has pharmacodynamic activity governed by 'time-dependent' activity. The fraction of time that the unbound drug concentration exceeds the MIC (fT >MIC ) for the dosing interval is the pharmacokinetic/pharmacodynamic (PK/PD) efficacy target for cefepime [4], and a target of 60-74% has been previously proposed [5][6][7][8]. For the currently approved cefepime product and combination agents in the pipeline [9,10], understanding cefepime disposition and variability is crucial to for optimal treatment of patients.…”
Section: Introductionmentioning
confidence: 99%